Effect of pineapple waste biochar and compost application on the growth and yield of pineapple varieties in Ghana - Hanyabui, Emmanuel; Frimpong, Kwame Agyei; Annor-Frempong, Festus; Atiah, Kofi (Frontiers in Agronomy, 2024)
Biochar is one of the commonly used soil amendments for sustainable agriculture. The effect of biochar on crop yields depends on the quality of the biochar, which is influenced by feedstock type and pyrolysis conditions. Sole application of pineapple waste biochar and compost, and their combination has not been rigorously investigated. In this study, we investigated the effects of pineapple waste biochar and compost applied solely or in combination on growth and yield of pineapple on a coastal savanna Acrisol in Ghana. The split-plot design with three replications was used, with pineapple varieties as the main plot and fertilizer application rates as the sub-plots. The results showed that sole application of biochar and compost or their combination as a soil amendment increased pineapple growth and yield as compared to the unamended soil. Biochar applied in combination with biochar/or inorganic NPK fertilizer significantly increased pineapple plant height, number of leaves which resulted in improved fruits yield of the three (sugar loaf, MD2 and smooth cayenne) pineapple varieties at maturity over control, sole application of biochar, compost and inorganic NPK fertilizer. Smooth cayenne variety outperformed MD2 and Sugar loaf variety. In conclusion, the results revealed that biochar applied solely or in addition with compost or inorganic NPK fertilizer has the capability to enhance soil quality and improve pineapple yield. Application of biochar in combination of compost/or inorganic NPK improves pineapple growth and yield.